A Highly Conserved Peptide Vaccine Candidate Activates Both Humoral and Cellular Immunity Against SARS-CoV-2 Variant Strains - Gao, Fengxia; Huang, Jingjing; Li, Tingting; Hu, Chao; Shen, Meiying; Mu, Song; Luo, Feiyang; Song, Shuyi; Hao, Yanan; Wang, Wang; Han, Xiaojian; Qian, Chen; et al. (Frontiers in Immunology, 2021)
ABSTRACT Facing the imminent need for vaccine candidates with cross-protection against globally circulating SARS-CoV-2 mutants, we present a conserved antigenic peptide RBD9.1 with both T-cell and B-cell epitopes. RBD9.1 can be recognized by COVID-19 convalescent serum, particularly for those with high neutralizing potency. Immunization with RBD9.1 can successfully induce the production of the receptor binding domain (RBD)-specific antibodies in Balb/c mice. Importantly, the immunized sera exhibit sustained neutralizing efficacy against multiple dominant SARS-CoV-2 variant strains, including B.1.617.2 that carries a point mutation (SL452R) within the sequence of RBD9.1. Specifically, SY451 and SY454 are identified as the key amino acids for the binding of the induced RBD-specific antibodies to RBD9.1. Furthermore, we have confirmed that the RBD9.1 antigenic peptide can induce a S448-456 (NYNYLYRLF)-specific CD8+ T cell response. Both RBD9.1-specific B cells and the S448-456-specific T cells can still be activated more than 3 months post the last immunization. This study provides a potential vaccine candidate that can generate long-term protective efficacy over SARS-CoV-2 variants, with the unique functional mechanism of activating both humoral and cellular immunity.